Propagation of high-power optical flat-topped beams in strongly nonlinear media - Yipeng Zheng (Elsevier, 2021)
We performed numerical experiments to investigate the propagation of high-power optical flat-topped beams through a strongly nonlinear medium, accounting for the diffraction, nonlinearity, and multiphoton absorption capabilities of the beams. We found that the uniform irradiance distribution of flat-topped beams can remain constant near the centre axis for a given propagation distance. A series of comparisons were conducted for flat-topped beams with different orders, which demonstrates that increasing the order reduces change of beam characteristic. Furthermore, we investigated the influence of input power on the propagation of flat-topped beams. Moreover, we numerically analysed the dynamics of the inner energy transfer and uniform irradiance decay of the flat-topped beam.